(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2010)
Keywords: faciparum malaria; intermittent peritoneal dialysis; multi-organ failure DOI: 10.3329/jcmcta.v20i2.5620 Journal of Chittagong Medical College Teachers’ Association 2009: 20(2):16-18